Simbolisme Busana Sulinggih dan Transformasi Nilai dalam Pendidikan Seni Keagamaan Hindu: Sebuah Studi Etnopedagogis di Bali - Abdhi Yasa, I Kadek (Jayapangus Press, 2025)
The Sulinggih attire in Balinese Hindu tradition embodies symbolic manifestations that integrate philosophical, spiritual, and pedagogical values, yet faces threats of meaning degradation due to globalization and the younger generation’s shift toward materialistic aesthetics. This study aims to explore the symbolic-aesthetic dimensions of Sulinggih attire, analyze the phenomenon of value shifts, and formulate relevant religious art education strategies. A qualitative ethnopedagogical method with an ethnographic design was employed through in-depth interviews, participatory observation, and document analysis (lontar manuscripts, curricula) of 16 attire components, involving Sulinggih priests, literary experts, and youth. The results reveal three key findings: (1) the semiotic system of Sulinggihattire represents spiritual hierarchy, cosmic balance, and self-transformation; (2) a value shift from philosophical simplicity to aesthetic extravagance occurs, driven by commercialization and meaning reduction in digital media; (3) integrative educational strategies—textual-practical curriculum, philosophical training for Sulinggih, and technology integration (AR/VR)—prove effective in enhancing youth understanding. Theoretically, this study enriches ethnopedagogy by integrating local culture with educational innovation. Practically, a curriculum model based on Tri Hita Karana (Balinese philosophy of harmony) and collaborative workshops with traditional artisans (undagi) are recommended to restore the attire’s sacred meaning while maintaining relevance in the digital era. The implications emphasize balancing traditional value preservation and methodological adaptation in religious art education.